A review of impact testing on marine composite materials: Part III - Damage tolerance and durability. (15th March 2018) - Sutherland, L.S.
Abstract: Composite materials are now used throughout the marine industry but their susceptibility to impact events is still an unresolved problem. The complex nature of the problem in terms of the distinct material and impact event parameters specific to marine applications has been discussed in parts I & II. Tolerance to impact damage is very often of greater concern than resistance to a catastrophic failure and hence the compression, flexural and other loading tolerance of marine composites to impact is reviewed here. Since in-service impacts will occur in the aggressive marine environment, studies on water absorption, temperature and repeated impact effects have also been discussed. Together with parts II and III, this paper gives a comprehensive review of 'marine impact on marine composites', providing a valuable resource for the marine industry and research fields.